PERAN KONSELING INDIVIDU DALAM MENGATASI PERILAKU MEMBOLOS SISWA MTs MUKHTAR SYAFA’AT BLOKAGUNG TEGALSARI BANYUWANGI - Alfina Shofi Afkarina; Mahmudah Mahmudah; Muhammad Imam Khaudli; Nur Anim Jauhariyah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Ditching behavior is a form of juvenile delinquency that reflects student violations in school rules and regulations that will harm themselves and others, such as missing subject matter. The purpose of this study was to determine the forms, factors that encourage students to play truant as well as to determine the methods of guidance and counseling used by BK teachers based on the factors encountered. As understood, the impact of truancy behavior is failure in learning, failure in learning. The research method used in this research is qualitative. The subjects in this study were students of MTs Mukhtar Syafa'at Blokagung Banyuwangi. Data collection techniques in this study were interviews to obtain information about forms, factors, and methods of guidance and counseling, observations to obtain other information that supported the data obtained and documentation to obtain data including descriptions of schools and student development. The causes of truancy behavior are problems that come from self, family, school, and environmental factors with truant behavior, namely sleeping in the dormitory, hanging out in the shop, truant in certain subjects because they don't like the teacher and chatting when they meet their friends.